2021
DOI: 10.1007/s11368-021-03061-3
|View full text |Cite
|
Sign up to set email alerts
|

Spatial enrichment assessment, source identification and health risks of potentially toxic elements in surface sediments, Central Asian countries

Abstract: Purpose Potentially toxic elements (PTEs), particularly metallic elements, are some of the most dangerous pollutants found in surface sediments due to their toxicity and persistence. Given the contamination-related issues for sediments in Central Asian countries (CACs), a combination of risk assessment and source apportionment was used in characterizing the pollution sources and source-specific risks of metallic elements in the sediments of CACs. Materials and methods Surface sediment samples collected from 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Also, the average concentrations of HMs were compared with previous relevant studies for other regions in CA (Table 1). It was found that the HM concentrations in surface sediments of the ADB were close to those throughout the CA, except for Zn, Cu and Ni (Wang et al, 2021a). Compared to the surface samples from the Caspian Sea region (CSR) and Issyk-Kul Lake region (IKLR), however, the sediments in the ADB had the highest mean concentrations of Cd, Cu and Cr, especially Cd, while the topsoil in IKLR had the highest average concentrations of Pb and Zn, and the surface samples from the CSR had the relatively high abundance of Ni (De Mora et al, 2004;Ma et al, 2018).…”
Section: Concentration Variations Of Metallic Elementsmentioning
confidence: 83%
See 2 more Smart Citations
“…Also, the average concentrations of HMs were compared with previous relevant studies for other regions in CA (Table 1). It was found that the HM concentrations in surface sediments of the ADB were close to those throughout the CA, except for Zn, Cu and Ni (Wang et al, 2021a). Compared to the surface samples from the Caspian Sea region (CSR) and Issyk-Kul Lake region (IKLR), however, the sediments in the ADB had the highest mean concentrations of Cd, Cu and Cr, especially Cd, while the topsoil in IKLR had the highest average concentrations of Pb and Zn, and the surface samples from the CSR had the relatively high abundance of Ni (De Mora et al, 2004;Ma et al, 2018).…”
Section: Concentration Variations Of Metallic Elementsmentioning
confidence: 83%
“…Assessing the spatial distribution of metals in surface sediments can be a good way to determine positions with higher HM contents and provide evidence of anthropogenic impacts (Chen et al, 2019;Wang et al, 2021a;Yang et al, 2021). To reduce the influence of particle size, and better understand geochemical characteristics and anthropogenic inputs of met-al elements, the spatial distribution of metal concentrations with normalized values were essential (Zeng et al, 2014;Zhou et al, 2021).…”
Section: Normalization and Spatial Distributions Of Metalsmentioning
confidence: 99%
See 1 more Smart Citation